2010
DOI: 10.1111/j.1600-0706.2010.18508.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting population heterogeneity in effects of North Atlantic Oscillations on seabird body condition: get into the rhythm

Abstract: Climatic influences on animal populations, mediated by changes in condition‐dependent survival or reproduction, have long intrigued ecologists. We analyzed links between winter North Atlantic Oscillations (NAO), a large scale climatic phenomenon affecting weather conditions over the North Atlantic and the Arctic, and average pre‐laying body mass in common eiders. Body mass is a good proxy for condition‐dependent reproductive output in this species. Time series links were assessed for two eider populations bree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 56 publications
1
56
0
Order By: Relevance
“…So far, many studies on seabirds breeding around the North Atlantic have demonstrated the influence of the NAO on life history traits and population dynamics (e.g. Wanless et al 2009, Descamps et al 2010, Sandvik et al 2012, Smith & Gaston 2012. As a 'weather package' , the NAO index is assumed to be a reliable proxy for North Atlantic climate, catching most of the variation in several atmospheric and oceanographic parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…So far, many studies on seabirds breeding around the North Atlantic have demonstrated the influence of the NAO on life history traits and population dynamics (e.g. Wanless et al 2009, Descamps et al 2010, Sandvik et al 2012, Smith & Gaston 2012. As a 'weather package' , the NAO index is assumed to be a reliable proxy for North Atlantic climate, catching most of the variation in several atmospheric and oceanographic parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In migratory birds, population attributes can be strongly affected by environmental factors encountered away from the Arctic breeding grounds [53,65,66]. Spring migration phenology, and hence timing of breeding, may be constrained by the timing of life-cycle phases preceding migration, by different climatic variations in the wintering areas and along the migratory route, or by depleted genetic variance in migration traits [67].…”
Section: Discussionmentioning
confidence: 99%
“…In several bird species, associations of the NAOI with vital rates have already been found (e.g. Forchhammer et al 1998;Grosbois and Thompson 2005;Crespin et al 2006;Descamps et al 2010;Zipkin et al 2010).…”
Section: Environmental Covariatesmentioning
confidence: 99%